Study of Integrated Run off River Hydro and Solar PV Power Generation Scheme in Sikkim (International Journal of Innovative Research in Engineering & Management, 2022)
Sikkim is naturally endowed with rich  Hydro Power potential. The State’s generation capacity  is contributed solely by the hydro stations. But recent  years these stations are encountering increasing number  of uncertain weathers, which resulted into shortfall of  precipitation during monsoon and higher abnormal  rainfall during pre-monsoon times. Though some of the  rivers are perennial but these uncertainty are creating  challenge for them. More over the state has a large  number of Run off river (RoR) hydro systems, which  has a limited storage capacity. This is practically  impossible to store the amount of water resource  required by the hydro power plant through the use of  such small pondage system. Neither this practice is  permitted. The uncertain whether creates threat to the  power supply, in this backdrop the present work aims to  integrate the existing RoR hydro power plant with a  reasonable amount of solar PV to maintain the supply  reliability throughout the year. The present work  involves a pre-HOMER analysis of load profile,  resources at the site and post-HOMER analysis and  discusses issues that are likely to affect/influence the  realization of the optimal solution.
Keywords: PV; Hydro; Run off river; HOMER; integrated energy